PENGARUH STRATEGI PEMBELAJARAN BERBASIS MASALAH TERHADAP HASIL BELAJAR MAHASISWA YANG MEMILIKI GAYA KOGNITIF BERBEDA - Risvirenol, Risvirenol (JSTT, 2015)
Instructional strategy the main component on intruction processes as a way to affecting student in Better learning process. There are a variety of strategy that a teacher may select depending on his/her need and the students’ condition. In the present study, the strategy used were problem besad learninf as the independent variable, the cognitive st as the moderating variable, and the learning outcome as the dependent variable. The study was aimed to examine: (1) the effect of differences in learning outcome between problem based learning with direct intruction in the teaching development of learners; (2) the differences influence learning as cognitive style; (3) the interaction between intruction strategy and cognitive style on learning outcomes. This study applied quasi-experiment using 2x2 factorial desing, sampel was 75 student. The instrument to measure the students’ learning outcome was an achievement test, while the one to measure the students’ individual cognitve style was an cognitve style questionnaire. The data collected in the study were post-test scores that were analyzed by inferential statistics in order to identify the significance of difference from the data of each group. The research result showed that 1) learning outcomes of students’ group problem based learning strategy significantly differences than direct instruction grup, 2) there was significant difference in learning outcomes students of field dependence cognitive style and field independence cognitive style, 3) there was significant interaction betwen instuction strategy and cognitive style toward learning outcomes of the students. Based on the Research results , it is suggested 1) to apply problem based learning as one of the intruction strategies in development of learners subject, 2) lecturers Seed to pay attention to student’ cognitive style before implementing instruction strategy.